MERAJUT KEARIFAN LOKAL MELALUI PROVERB PADA ERA GlOBAL - Ana Thereana (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
Abstract— Language has a central role in intellectual, social, and emotional development. Today, people are very easily ignited, angry, brutal, abusive, and vulgar without being able to control their lusts, such as demonstrators' rude behavior in demonstrations that are often aired on television. The value of local wisdom that polite, friendly, respectful, wise, and religious as if more and more eroded. As a civilized and dignified nation, such a situation is clearly unfavorable to the future of the nation, especially in the birth of future generations of the nation. Therefore, it takes education oriented to the character of the nation, which is not just pursuing the interests of thought, memorization, and logic but also need to pay attention and integrate moral issues and nobility character. Through language education and literature is expected to play a dignified nation character building as well as develop the potential of learners to be a figure of human Indonesia who believe and piety to God Almighty, morals, healthy, knowledgeable, intelligent, creative, and independent. Proverbs are (1) proverbs / groups of words or sentences that remain in their order, usually to define a particular purpose; (2) compact phrases, expressions, comparisons, parables, counsel, principles of life, or rules of conduct. Conservation of proverbs as a supporter of local wisdom and character education needs to be done. Conserving proverbs means preserving and protecting local proverbs and wisdom. Proverbs need to be conserved in various ways. Conservation of proverbs is useful as a supporter of local wisdom and character education. Character is a series of individual psychological traits that affect personal ability and tendency to function morally. Keywords— Value of proverb wisdom, local wisdom, morals. Abstrak— Bahasa memiliki peran sentral dalam perkembangan intelektual, sosial, dan emosional. Dewasa ini, masyarakat sangat mudah tersulut emosinya, pemarah, brutal, kasar, dan vulgar tanpa mampu mengendalikan hawa nafsunya, seperti perilaku para demonstran yang berkata kasar dalam berunjuk rasa yang seringkali ditayangkan di televisi. Nilai kearifan lokal yang santun, ramah, saling menghormati, arif, dan religius seakan semakin terkikis. Sebagai bangsa yang beradab dan bermartabat, situasi yang demikian itu jelas tidak menguntungkan bagi masa depan bangsa, khususnya dalam melahirkan generasi masa depan bangsa. Oleh karena itu, dibutuhkan pendidikan yang berorientasi pada karakter bangsa, yang tidak sekadar memburu kepentingan pikir, menghafal, dan logika tetapi juga perlu memperhatikan dan mengintegrasi persoalan moral dan keluhuran budi pekerti. Melalui pendidikan bahasa dan sastralah diharapkan dapat berperan membangun karakter bangsa yang bermartabat sekaligus mengembangkan potensi peserta didik agar menjadi sosok manusia Indonesia yang beriman dan bertakwa kepada Tuhan yang Maha Esa, berakhlak mulia, sehat, berilmu, cerdas, kreatif, dan mandiri. Proverb adalah (1) peribahasa/ kelompok kata atau kalimat yang tetap susunannya, biasanya mengiaskan maksud tertentu; (2) ungkapan atau kalimat ringkas, padat, berisi perbandingan, perumpamaan, nasihat, prinsip hidup, atau aturan tingkah laku. Konservasi peribahasa sebagai pendukung kearifan lokal dan pendidikan karakter perlu dilakukan. Mengonservasi peribahasa berarti mengawetkan dan melindungi peribahasa dan kearifan lokal.Peribahasa perlu dikonservasi melalui berbagai cara. Konservasi peribahasa berguna sebagai pendukung kearifan lokal dan pendidikan karakter. Karakter merupakan serangkaian ciri-ciri psikologis individu yang mempengaruhi kemampuan pribadi dan kecenderungannya berfungsi secara moral. Kata Kunci— Nilai kearifan proverb, kearifan lokal, moral.